Governance, regulation, and privatization in the Asia-Pacific Region - Itō, Takatoshi, 1950-; Krueger, Anne O. (NBER-East Asia Seminar on Economics (Series), 2004)
Over the last twenty-five years, there has been an acceleration in the move from government regulation towards privatization. Governance, Regulation, and Privatization in the Asia-Pacific Region is the first thoroughgoing account of the relative success of the different approaches to privatization as undertaken in Korea, China, Australia, and Japan. In most contexts, privatization is expected to yield greater efficiency and cost effectiveness while avoiding the corruption and bloated budgets of government regulation or monopoly control. But broad-scale privatization, if ill designed, has also.